Herpesviruses and Their Host Cells: A Successful Liaison. Issue 3 (March 2017) - Adler, Barbara; Sattler, Christine; Adler, Heiko
Abstract : During a long history of coevolution, herpesviruses have reached a fine-tuned balance with their hosts, allowing them to successfully persist and spread to new hosts without causing too much damage. Only under certain circumstances, as in neonates or immunocompromised individuals, they may cause serious diseases. The delicate balance between herpesviruses and their hosts results from interactions of a great variety of viral and cellular factors which together shape the tropism for a particular host, tissue, or cell. Understanding these interactions will provide insight into the viral life cycle and cell biology in general. Moreover, it will also facilitate comprehension of herpesvirus pathogenesis, enabling the development of new strategies to combat herpesviruses in cases where they cause disease. Trends: Herpesvirus host cells are defined by their susceptibility to productive or latent infection. Herpesvirus host cells contribute to navigation of viruses through the infected host, either directly as vehicles or indirectly by shaping the glycoprotein content of viral envelopes. Herpesviruses can manipulate their host cells by changing their differentiation status. Herpesviruses stand out by a highly redundant equipment with regulatory proteins or noncoding RNAs. This redundancy stands in the way of clearing a herpesvirus infection. The development of new antiherpesviral drugs or vaccines, and the application of herpesviruses as oncolytic agents, vaccine- or gene-therapy vectors depends on understanding interactions between viral and host cell factors.